Mechanisms of Creative Cultural Tourism in Hin Khon Subdistrict,Lam Plai Mat District, Buriram Province: Mechanisms of Creative Cultural Tourism in Hin Khon Subdistrict,Lam Plai Mat District, Buriram Province - phutthiphongchaicharn, thanyarat; Sivarangsirat, Pharanroj; Promthong, Juthamas (RATANABUTH JOURNAL, 2024)
Hin Khon Community, Lamplai Mat District, Buriram Province is a community with diverse tourism potential in nature. Culture, Antiquities and Wisdom Engaging Activities The involvement of people in the community and government agencies to help promote and develop creative cultural tourism is an important mechanism in cultural tourism management. Therefore, the objectives of the research are 1) to study the potential of cultural tourism sites in Hin Khon sub-district and 2) to analyze the mechanism of creative cultural tourism in Hin Khon sub-district. The main informants are stakeholders in creative cultural tourism. 1 picture of 29 people, including religious leaders, community leaders, village sages, People in the community Culture of Buriram Province Ban Hin Khon School and Hin Khon Sub-district Administrative Organization The research tools are interviews and group discussions. The results show that the potential of Ban Hin Khon tourist attractions consists of 1) resources, 2) facilities, 3) access to tourist attractions, 4) community participation, 5) management, and 6) community tourism activities. Tourism management, benefit allocation, tourism monitoring and evaluation. Therefore, the participation of people in the community has created a creative cultural tourism mechanism. Hin Khon Subdistrict R = Resources is the community’s resources that attract tourists to visit, including tourist attractions and wisdom of the Hin Khon community, A = Activity is the wisdom that the community brings to the community as a learning activity with practical experience, C = Creative is the development of creative potential through tourism activities, P = Public participation is the management of tourism with the participation of the public sector, and A = Agency support is the support from government agencies.